1991
DOI: 10.1007/bf00370571
|View full text |Cite
|
Sign up to set email alerts
|

Different types of blockers of the intermediate-conductance outwardly rectifying chloride channel in epithelia

Abstract: Epithelial chloride channels can be blocked by various inhibitors, which show considerable differences in their molecular structure. In the present patch-clamp study, we compared different blockers of one type of epithelial Cl- channel with respect to their inhibitory potency. We applied the blockers to excised inside-out-or outside-out-oriented membrane patches of cultured HT29 colon carcinoma and respiratory epithelial cells (REC) containing the outwardly rectifying intermediate-conductance (ICOR) chloride c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 39 publications
3
40
0
Order By: Relevance
“…However, in contrast to all but one of these channels, GC1 does not show inactivation at positive potentials. Additionally, the values for half-maximal inhibition of GCc by DIDS, 41 to 9/M, are well within the range for inhibition of DIDS on a number of Cl-channels (Tilmann et al 1991;Lewis et al 1993;Diaz et al 1993). …”
Section: Methodsmentioning
confidence: 87%
“…However, in contrast to all but one of these channels, GC1 does not show inactivation at positive potentials. Additionally, the values for half-maximal inhibition of GCc by DIDS, 41 to 9/M, are well within the range for inhibition of DIDS on a number of Cl-channels (Tilmann et al 1991;Lewis et al 1993;Diaz et al 1993). …”
Section: Methodsmentioning
confidence: 87%
“…Control, preconditioned, and oxygenated baseline (240-minute incubation in an O 2 atmosphere at 37°C) myocytes were simultaneously treated with either of 2 selective Cl -channel blockers that have distinct molecular structures and inhibitory mechanisms, 10 mol/L IAA-94 or 1 mol/L 5-nitro-2-(3-phenylpropylamino)benzoic acid (NPPB) (Research Biochemicals International Inc), 30,31 or they were treated with the vehicle of either drug (0.03% and 0.09% ethanol for IAA-94 and NPPB, respectively). The blocker was initially added to the myocyte suspension either 10 minutes before IP or just before the long SI (IAA-94 only).…”
Section: Experimental Protocol For Ventricular Myocytesmentioning
confidence: 99%
“…IAA-94 was added either 10 minutes before IP or just before the long SI, whereas NPPB was added before IP only. Myocyte viability was assessed at the following time points ( * ): end of stabilization, before long SI, during long SI alone (30,60,90,120, and 180 minutes), and at the end of SI (45 minutes) and during SR (15,60, and 120 minutes) in the ischemia/reperfusion protocol. channels play a role in the protection of IP during the long ischemia, hearts were subjected to the same control and IP protocols with a 10-minute exposure to IAA-94 or NPPB, at the same concentrations used in the isolated myocyte model, before the long ischemia.…”
Section: Experimental Protocol For Isolated Heartsmentioning
confidence: 99%
“…Pharmacology of the CO-current NPPB has been reported to be a most potent blocker for intermediate-conductance outwardly rectifying Cl-channel in HT29 epithelial cells (Tilmann et al 1991) and also was reported to block the Cl-pathways involved in the regulatory volume decrease in intestinal 407 cells (Kubo & Okada, 1992) and virus-transformed ciliary epithelial cells . In our study the volume-sensitive Cl currents showed a high sensitivity to NPPB with an IC50 of 13-4 uM, which compares with 25 uM for a volumeregulatory Cl-channel in cultured human intestinal 407 epithelial cells (Kubo & Okada, 1992).…”
Section: ~~mentioning
confidence: 99%